FINANCIAL COMPENSATION HAS A HUGE IMPACT TO NON-PERMANENT TEACHER’S (GTT) WORKING PRODUCTIVITY IN SMP N 2 JEMBER - Reni Dwi Agustina; Bagus P Yudhia K; Supardi Supardi (MBA - Journal of Management and Business Aplication, 2018)
This article research entitled " Financial compensation has a huge impact to NonPermanent Teacher’s working productivity (GTT) in SMP N 2 Jember". This study attemps to analyze and examine the impact and the effect of financial compensation on the level of productivity of Non-Permanent Teachers (GTT) of SMP N 2 Jember, either simultaneously or partially. This research belongs to explanatory research survey. The location of this research is SMP N 2 Jember. The Independent variable in this study is financial compensation (X) which consist of salary (X1), courses allowances (X2) and overtime wages (X3), while the dependent variable in this is work productivity of employee (Y). The Population in this research are all non permanent teachers (GTT) at SMP N 2 Jember which also become the sample. To analize the data, the researcher uses SPSS (Statistical Product and Service Solution) version 10. Based on the results of the data, it is known that financial compensation (salary, courses allowances and overtime wages) are significant and has a very important role to incourage the productivity of Non-Permanent Teachers (GTT) in SMP Negeri 2 Jember either partially or simultaneously. In the partial test results which were proved by the score of t-count of each independent variable that are salary, courses allowances and overtime wages are higher than its t-table, so Ho is rejected and H1 is accepted. The effective contribution of the three variable financial compensation (salary, courses allowances and overtime wages) to the productivity of Non-Permanent Teachers (GTT) in SMP Negeri 2 Jember is also very large at 96.0% in the courses allowances variable as the most dominant variable. The conclusion is there are strong and significant impact of financial compensation towards work productivity of non permanent teachers in SMP N 2 Jember. So that to increase the work productivity, hence financial compensation must be balanced and must be improved also.